2019
DOI: 10.1016/j.cbi.2019.06.032
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic exposure to arsenic and high fat diet induces sex-dependent pathogenic effects on the kidney

Abstract: Both obesity and arsenic exposure are global public health problems that are associated with increased risk of renal disease. The effects of whole-life exposure to environmentally relevant levels of arsenic within dietary high fat diet on renal pathogenesis were examined. In this study, C57BL/6J mice were parentally exposed to 100ppb arsenic before conception. After weaning, both male and female offspring were maintained on 100ppb arsenic and fed either a normal (LFD) or high fat diet (HFD). At 10 and 24 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…A reduction in liver and kidney weight was also observed in females and males of the F0 generation and later in the F2 and F3 generations of the arsenic lineage but only in liver weight. Studies have reported a significant reduction in the weight of the liver 58 and kidneys 59 , 60 of rats and mice exposed to arsenic. In addition to the effect of arsenic on hepato-renal organ somatic indices, a mechanism that could explain the weight loss is that arsenic can contribute to blockage of cellular glucose uptake due to a carbohydrate depletion, promoting that cellular glucose metabolism cannot be ruled out, besides the diverse mechanisms related to an increased risk of diabetes mellitus in animal models 61 .…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in liver and kidney weight was also observed in females and males of the F0 generation and later in the F2 and F3 generations of the arsenic lineage but only in liver weight. Studies have reported a significant reduction in the weight of the liver 58 and kidneys 59 , 60 of rats and mice exposed to arsenic. In addition to the effect of arsenic on hepato-renal organ somatic indices, a mechanism that could explain the weight loss is that arsenic can contribute to blockage of cellular glucose uptake due to a carbohydrate depletion, promoting that cellular glucose metabolism cannot be ruled out, besides the diverse mechanisms related to an increased risk of diabetes mellitus in animal models 61 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Most studies were focused on the effect of inorganic arsenic over short term duration. 12 Therefore, this study aimed to explore the effects of chronic low dose exposure of or ganic ars enic on the r ats ' kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been associated with many types of cancer (skin, lung, liver, and bladder) [16]. Nutrition deficiency in woman also found due to arsenic exposure and has been reported in various studies [17][18][19]. However the organic arsenic is less toxic than inorganic arsenic.…”
Section: Introductionmentioning
confidence: 99%